Greek Turkish Clash in the novels “The War between Ottomans and Greeks” of Nichola Elias and “The Story of Prisoner of War” of Stratis Doukas - Moussa, Shaker (Σύγκριση/Comparaison/Comparison, 2020)
It can be said that the destruction of Asia Minor appeared strongly in Greek literature, especially in the works of the generation of the 1930s, who lived through this period, and saw the suffering experience the Greek emigrants passed, coming from Asia Minor and the narrated stories of their suffering. The reading of the work leads to the conclusion that the Christian faith and ideology of the author appears in the work. In spite of the negative spirit that dominates the work, especially at the beginning, we find that this negative spirit is phasing out gradually, thanks to the good deeds of the enemy. This happens because of the good behavior of the Turks enemies. The sense of war and the barbarity of other, one can observe it from the beginning of the work. The writer attempts to emphasize the state of violence and risk that he has been subject to, and how the enemy has been trying to kill them. But it seems that the conflict, as portrayed by the writer, depends not only on the soldiers, but also the common people. We can note that, over their attempts to kill all the remaining Greeks, which made them chasing people trying to flee their lives.